Examining the links between household livelihood resilience and vulnerability: disaster resettlement experience from rural China - Liu, Wei; Liu, Jiayi; Xu, Jie; Li, Jie; Feldman, Marcus (Frontiers in Environmental Science, 2024)
There has been a call for more quantitative evidence about the links between livelihood resilience and livelihood vulnerability in the context of disaster resettlement. This study uses data from a sample of 657 individuals from the relocation area of Ankang prefecture in southern Shaanxi, China. The resilience of rural household livelihood systems is quantified in terms of two dimensions of general resilience and specific resilience using the spatial vector method from systems engineering. The IPCC framework was used to measure three dimensions of livelihood vulnerability: exposure, sensitivity, and adaptability, and a threshold regression model was applied to investigate the impacts of livelihood resilience on livelihood vulnerability. Results show that: (ⅰ)livelihood vulnerability of relocated households (-0.042) was significantly lower than that of local households (0.091), while relocated households in the process of livelihood reconstruction had a certain degree of vulnerability risk. (ⅱ) there is a significant threshold effect of livelihood resilience on livelihood vulnerability of rural households. (ⅲ) increasing livelihood resilience significantly reduced the degree of vulnerability of rural households, and the marginal effect of general resilience on livelihood vulnerability shows a decreasing trend. Specific resilience has a positive influence on livelihood vulnerability before it exceeds the threshold, but the effect disappears above the threshold of resilience. (ⅳ) The threshold value of livelihood resilience of local households (0.5039) is generally lower than that of relocated households (0.6548), and relocation does improve the ability of rural households to resist uncertainty risks. It is necessary for local governments to formulate more targeted policies to reduce the livelihood vulnerability of rural households and thereby promote sustainable livelihood development.